Transverse excitations of ultracold matter waves upon propagation past abrupt waveguide changes - Koehler, M.; Bromley, M. W. J.; Esry, B. D (My University, 2005)
The propagation of ultracold atomic gases through abruptly changing waveguide potentials is examined in the limit of noninteracting atoms. Time-independent scattering calculations of microstructured waveguides with discontinuous changes in the transverse harmonic binding potentials are used to mimic waveguide perturbations and imperfections. Three basic configurations are examined: steplike, barrierlike, and well-like with waves incident in the ground mode. At low energies, the spectra rapidly depart from single moded, with significant transmission and reflection of excited modes. The high-energy limit sees 100% transmission, with the distribution of the transmitted modes determined simply by the overlap of the mode wave functions and interference.